SOSIAL EKONOMI PEKARANGAN BERBASIS KAWASAN DI PERDESAAN DAN PERKOTAAN TIGA PROVINSI DI INDONESIA - Harmi Andrianyta; Maesti Mardiharini (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2015)
ABSTRACTSocial Economic of Homeyard Based on Rural and Urban Areas in Three Provinces of Indonesia. Homeyard in urban and rural areas is a pivotal source of food, family nutrition and household economics. This study aims to discuss the existence of homeyard in urban and rural areas from the socio-economic perspective. The research was conducted  in three provinces: South Kalimantan, Central Java and South Sumatra during September and October 2012. The research used cluster-based involving 50 respondents that represent people in urban and rural areas. Data were collected through interviews including: the respondents’ characteristics, the choice of plants, the plant arrangement, the type of work and tenure. The data were analyzed using descriptive analysis (cross tabulations), a comparative analysis of median values (t test), χ2 analysis (chi-square) and correlation analysis. The results showed that there are differences in the characteristics of the homeyard management aspects of demographic, social, cultural, economic and natural resources in both areas. It can be concluded that, the existence of the management of the homeyard in urban and rural areas plays a strategic role as a source of household economy, even though in a different management, especially in the diversity of cultivated plants and pattern of arable land. As an implication, homeyards need to be considered as a potential economic and productive resource in agricultural development policy. Keywords: Homeyard, social economic, rural areas, urban areas ABSTRAK          Pekarangan di perkotaan dan perdesaan berpotensi sebagai penyedia sumber bahan pangan, gizi keluarga dan ekonomi rumah tangga. Pengkajian bertujuan untuk membahas eksistensi pekarangan di perkotaan dan perdesaan dalam perspektif sosial ekonomi. Pengkajian dilakukan di Provinsi Kalimantan Selatan, Jawa Tengah dan Sumatera Selatan pada bulan September dan Oktober 2012. Rancangan pengkajian disusun berdasarkan pengelompokkan kawasan perkotaan dan perdesaan melibatkan 50 orang responden mewakili daerah perkotaan dan perdesaan. Data dikumpulkan melalui wawancara meliputi: karakteristik responden, pemilihan jenis tanaman, penataan tanaman, jenis pekerjaan dan penguasaan lahan. Data yang terkumpul dianalisis secara deskriptif (tabulasi silang), analisis perbandingan nilai tengah (uji t), analisis χ2 (chi square) dan korelasi. Hasil pengkajian menunjukkan bahwa terdapat perbedaan karakteristik pengelolaan pekarangan dari aspek demografi, sosial budaya, sumber daya alam dan ekonomi di kedua kawasan. Kesimpulan eksistensi pengelolaan pekarangan di perdesaan dan perkotaan memiliki peran strategis sebagai sumber ekonomi rumah tangga, meskipun dalam pengelolaannya berbeda terutama dalam keragaman jenis tanaman yang diusahakan dan pola penataannya. Sebagai implikasinya, dalam kebijakan pembangunan pertanian keberadaan lahan pekarangan perlu dipertimbangkan sebagai sumberdaya ekonomi produktif yang potensial. Kata kunci: Pekarangan, sosial ekonomi, perdesaan dan perkotaan.